Peran Pegawai dalam Meningkatkan Kualitas Layanan pada Sektor Publik - Angye Mareta Y; Dasman Lanin; Asnil Asnil (Public Service and Governance Journal, 2025)
High quality public services are a key indicator of effective government performance. In this context, the role of employees as the frontline executors of public service delivery is crucial in determining public satisfaction and trust toward public institutions. This study aims to explore the contribution of employees in enhancing public service quality through a literature review approach. Data were collected from various scholarly sources, including journals, books, and research reports related to public service and human resource management in the public sector. The findings indicate that the quality of public services is significantly influenced by several employee-related factors, such as competence, work ethics, integrity, innovation, and adaptability to technology and evolving public needs. Furthermore, organizational culture and leadership style also play a supportive role in reinforcing employees' contributions to excellent service delivery. This study emphasizes the importance of strengthening employee capacity through continuous training, performance evaluation, and the creation of a work environment that promotes accountability and professionalism.